Childhood Obesity and the Relationship to Well-Child Visits - (:unkn) unknown (My University, 2012)
Trends during the past 20 years have revealed a dramatic increase in childhood obesity in the United States. At present, approximately nine million children over 6 years of age are considered obese (Institute of Medicine [IOM], 2011). According to (American Academy of Pediatrics [AAP], 2009) the protocol for obesity care for youth is to monitor the body mass index (BMI) routinely (at least annually) and offer appropriate counseling and guidance to children and their families. A report in the literature indicated that the number of children attending yearly well-child visits that include measurement of BMI is well below the AAP recommendation (Selden, 2006). The dramatic increase in childhood obesity raises the question of what is the healthcare provider’s level of involvement in prevention, identification, and treatment of childhood obesity, and the prevalence of childhood obesity. The purpose of this retrospective exploratory design was to examine the number and content of well-child visits and describe the difference in attendance and content of the healthcare visit based on type of provider. Data were accessed through medical records of two clinics in the rural Midwest to describe the well-child visits and childhood obesity in children 6-11 years of age. However, there was an increase in frequency of healthcare visits for children who were being cared for by pediatricians. Regardless of healthcare provider, the rates of overweight and obesity reported during the healthcare visits did not follow a specific upward or downward trend. Children with an elevated BMI did not have providers consistently documenting a secondary diagnosis of overweight or obese. No follow up of one month for children whose BMI was in the obese category was found. The frequency of secondary diagnosis and intervention was consistent for children who saw pediatricians, yet inconsistent for children who saw family practice providers, physician assistants, and nurse practitioners, suggesting that providers vary in diagnosing and offering interventions for obese children. Examining the content of healthcare visits, more specifically the physical exam and education provided, nurses may acquire greater insight into gaps in strategies for health promotion and interventions that address the outcomes of overweight and obesity.
Keywords: Childhood Obesity